Program Kampung Moderasi Beragama (KMB) sebagai Perwujudan Toleransi Antar Umat Beragama di Desa Ngablak - Lestari, Nurul Dwi (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
As a pluralistic country consisting of various ethnicities, cultures and religions, Indonesia has various differences that have the potential to cause conflict. Therefore, the government legalized religious moderation villages which aim to create a safe, comfortable and intact environment, as well as compassion for all citizens. This service activity aims to dig up information related to the implementation of the KMB (Religious Moderation Village) program in Ngablak Village, Banyakan District, Kediri Regency. This service activity uses the PAR (Participatory Action Research) method with three stages, namely the planning, implementation and evaluation/reflection stages. The results of this service activity show that the implementation of the KMB in Ngablak Village can be used as an inspiring example for other villages in building religious harmony and resolving conflicts in a peaceful manner. The KMB program receives support from both the central government and regional governments, through the provision of budgets, training and technical guidance to provide optimal results.